2000
DOI: 10.1159/000014223
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Treatment Effects on Lung Structure and Type II Cells of Preterm Ventilated Lambs

Abstract: We evaluated surfactant treatment effects on lung morphology and alveolar type II cells of preterm ventilated lambs. Lambs were ventilated for 10 h following treatment of the right lung with natural surfactant. Lung parenchyma from the surfactant-treated right and the untreated left lung was compared morphometrically. Mechanical ventilation without surfactant resulted in distention of alveolar ducts accompanied by shallowing and loss of well-defined alveoli without disruption of collagen or elastin fibers. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This is supported by the finding of an almost double risk of BPD in the group exposed to beta-methasone when birth weight and degree of prematurity are taken into account. The lack of association between the use of pulmonary surfactant with the development of BPD found in this study has been shown by others [9,26,27] but it is interesting to see that the more severe form of BPD was reduced in favor of milder disease with its use.…”
Section: Impact Of Use Of Antenatal Corticosteroids and Pulmonary Surfactantsupporting
confidence: 58%
“…This is supported by the finding of an almost double risk of BPD in the group exposed to beta-methasone when birth weight and degree of prematurity are taken into account. The lack of association between the use of pulmonary surfactant with the development of BPD found in this study has been shown by others [9,26,27] but it is interesting to see that the more severe form of BPD was reduced in favor of milder disease with its use.…”
Section: Impact Of Use Of Antenatal Corticosteroids and Pulmonary Surfactantsupporting
confidence: 58%
“…The high PIP of up to 40-50 cmH 2 O for the first 15 min were needed to clear the airways of fluid. Ventilation without surfactant results in over distention of the open lung because of the non-uniform surface tensions throughout the lung (32). …”
Section: Discussionmentioning
confidence: 99%
“…The preterm sheep lung at 130 d GA also is very surfactant deficient, and ventilation of the surfactant-deficient preterm lung causes nonuniform inflammation characterized by overinflation adjacent to regions of atelectasis (10). We treated the lambs with surfactant to minimize regional overdistention and to permit ventilation with lower pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The preterm fetal lung does not have increased permeability to protein relative to the mature lung (9). Therefore, the increased permeability that occurs in ventilated preterm lungs is thought to result from the effects of nonuniform inflation on a structurally immature and surfactant-deficient lung that contains insufficient collagen and elastin (10,11). The immature lung also has decreased host defense surfactant protein (SP)-A and SP-D and has immature immune systems with depressed second messenger responses making it potentially more susceptible to endotoxin-induced injury (12,13).…”
mentioning
confidence: 99%